PENGEMBANGAN LEMBAR KERJA SISWA(LKS)MATEMATIKA BERBASIS MASALAH UNTUK KELAS VIII SMP PADA MATERI LINGKARANI - wati, sasra (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2016)
The purpose of this study was to determine the development process based problems LKS valid and practical problems in the material circle. the type of research was the development of research (Research and Development), which consists of three stage, namely, the definition phase (Define), the design (Design), and development (Develop). The subjects were students of class VIII SMP N 1 Kepenuhan Â in the second semester of academic year 2015/2016. The instrument used in this study was the validation sheet and questionnaire practicalities. The process undertaken to get a valid LKS includes the step of defining, designing and development. At this stage of development LKS validator validated to four people with an average gain of 3.14 with the validation of a valid category. While the practicalities obtained based testing and assessment by an expert using a questionnaire practicalities expert, junior high school teacher, and eighth grade students of SMP N 1 Kepenuhan, with an average of 77% with the practicality of a practical category. So it can be concluded that based LKS valid and practical problems.